Identification of Bacteria on Housefly Exoskeletons (Musca domestica) collected in Universitas Negeri Makassar - Audriansyah, Lulu Ulfah; Daud, Firdaus; Syamsiah (Jurusan Biologi Universitas Negeri Makassar, 2025)
The housefly (Musca domestica) is a vector that can spread bacteria through its body organs. This study aims to identify the bacteria on the exoskeleton of houseflies. The samples were collected from boarding houses, Biology department and postgraduate program of Universitas Negeri Makassar using insect nets. Morphological observations were conducted on selective media (EMBA, MSA, and TCBSA), followed by Gram staining and biochemical tests. The results revealed six types of bacteria: Enterobacter sp., Escherichia coli, Staphylococcus aureus, Staphylococcus epidermidis, Vibrio cholerae, and Vibrio parahaemolyticus. Escherichia coli was found on houseflies collected from boarding houses. Staphylococcus aureus, Staphylococcus epidermidis, and Escherichia coli were identified on houseflies from the postgraduate campus. Meanwhile, Enterobacter sp., Staphylococcus aureus, Vibrio cholerae, and Vibrio parahaemolyticus were found on houseflies from the Biology department campus. These findings indicate that houseflies from the Biology department campus harbored a greater quantity and diversity of bacteria compared to samples from other locations.